Ten-Year Poverty Alleviation Effect of the Medical Insurance System on Families With Members Who Have a Non-communicable Disease: Evidence From Heilongjiang Province in China - Qi Xia; Lichun Wu; Wanxin Tian; Wenqing Miao; Xiyu Zhang; Jing Xu; Yuze Li; Baoguo Shi; Nianshi Wang; Huiying Yang; Zhipeng Huang; Huiqi Yang; et al. (Frontiers Media S.A., 2021)
Aims: Non-communicable diseases (NCD) drag the NCD patients' families to the abyss of poverty. Medical insurance due to weak control over medical expenses and low benefits levels, may have actually contributed to a higher burden of out-of-pocket payments. By making a multi-dimensional calculation on catastrophic health expenditure (CHE) in Heilongjiang Province over 10 years, it is significant to find the weak links in the implementation of medical insurance to achieve poverty alleviation.Methods: A logistic regression was undertaken to predict the determinants of catastrophic health expenditure.Results: The average CHE of households dropped from 18.9% in 2003 to 14.9% in 2013. 33.2% of the households with three or more NCD members suffered CHE in 2013, which was 7.2 times higher than the households without it (4.6%). The uninsured households with cardiovascular disease had CHE of 12.0%, which were nearly 10% points lower than insured households (20.4-22.4%). For Medical Insurance for Urban Employees Scheme enrolled households, the increasing number of NCD members raised the risk of impoverishment from 3.4 to 20.0% in 2003, and from 0.3 to 3.1% in 2008. Households with hospital in-patient members were at higher risk of CHE (OR: 3.10-3.56).Conclusions: Healthcare needs and utilization are one of the most significant determinants of CHE. Households with NCD and in-patient members are most vulnerable groups of falling into a poverty trap. The targeting of the NCD groups, the poorest groups, uninsured groups need to be primary considerations in prioritizing services that are contained in medical insurance and poverty alleviation.